2018
DOI: 10.1016/j.clinthera.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Peripheral Neuropathy: Epidemiology, Diagnosis, and Pharmacotherapy

Abstract: Clinical recognition of DPN is imperative for allowing timely symptom management to reduce the morbidity associated with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
275
1
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(299 citation statements)
references
References 180 publications
(151 reference statements)
3
275
1
20
Order By: Relevance
“…Symptoms may be vague, described as a tight feeling or abnormal sensation in the soles of the feet, intolerance of tactile stimuli (inability to wear socks or touch bedsheets), or a sensation of restless legs. The distribution of symptoms may have a length dependent or non-length dependent pattern that affects the limbs, trunk, face, or it may have a combination of patterns 12404142. Depending on the underlying cause, the onset of symptoms may be gradual, with slowly progressive worsening, or subacute with more rapid progression.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms may be vague, described as a tight feeling or abnormal sensation in the soles of the feet, intolerance of tactile stimuli (inability to wear socks or touch bedsheets), or a sensation of restless legs. The distribution of symptoms may have a length dependent or non-length dependent pattern that affects the limbs, trunk, face, or it may have a combination of patterns 12404142. Depending on the underlying cause, the onset of symptoms may be gradual, with slowly progressive worsening, or subacute with more rapid progression.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…42154 Most neuromuscular experts advocate for the use of electrodiagnostic studies in distal symmetric polyneuropathy if the diagnosis is known or unknown 155. Several studies have shown that electrodiagnostic studies in this population can often change the diagnosis and management 156157158.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…18 In this month's Topic Update, Dr. Zohaib Iqbal, Institute of Aging and Chronic Disease, University Hospital Aintree, University of Liverpool (Liverpool, United Kingdom), provides a critical review of current literature on the diagnosis and treatment of DPN, with a focus on the treatment of neuropathic pain in DPN. 19 Appropriate control of blood glucose and the management of the risk factors for cardiovascular disease substantially reduce the risk for microvascular and macrovascular complications among people with type 1 diabetes. 20 Diabetes control among patients with type 1 diabetes has been shown to improve with continuous subcutaneous insulin infusion (CSII), delivered via an insulin pump, 21 and a significant body of evidence accumulated over the past 25 years supports the efficacy of subcutaneous insulin delivered via a pump.…”
Section: Emerging Diabetes Research From Early Investigatorsmentioning
confidence: 99%
“…So when I talk of negative sensory symptoms this includes the feeling of deadness and numbness, feeling that a person is wearing gloves and stockings. Positive symptoms are ones that tend to trouble the patients certainly a lot more; these include electric shock-like feelings, aching, tightness, hypersensitivity to touch, burning and prickling and all of these can cause a considerable amount of pain and discomfort [4].…”
mentioning
confidence: 99%
“…[For further review and for further reading, Dr Alam would suggest a paper which he published in Clinical Therapeutics 2018 by the name of ''Diabetic Peripheral Neuropathy: Epidemiology, Diagnosis, and Pharmacotherapy'' [4]. This a detailed paper looking at the epidemiology and has detailed sections on pharmacotherapy.…”
mentioning
confidence: 99%